High-resolution magnetic resonance imaging of intracranial vessel walls: Comparison of 3D T1-weighted turbo spin echo with or without DANTE or iMSDE - Cho, Se Jin; Jung, Seung Chai; Suh, Chong Hyun; Lee, Jung Bin; Kim, Donghyun (PloS one, 2019)
The black-blood (BB) technique was developed to suppress the signal from blood and cerebrospinal fluid (CSF) to provide improved depiction of vessel walls. The aim was to compare three-dimensional turbo spin echo T1-weighted imaging (3D TSE T1WI) with or without two BB techniques (delay alternating with nutation for tailored excitation [DANTE], and improved motion-sensitized driven equilibrium [iMSDE]) for high-resolution magnetic resonance imaging (HR-MRI) of the vessel walls of intracranial arteries. Prospective. Fourteen healthy volunteers who underwent 3D T1WI for examination of intracranial vessel walls. 3 Tesla, 3D TSE T1WI (SPACE and BrainVIEW) and BB (DANTE and iMSDE). SPACE with or without DANTE, and BrainVIEW with or without iMSDE, were acquired in each subject. Two neuroradiologists independently assessed image quality, vessel wall delineation, BB effect, CSF, and acceptability using visual scoring systems, and measured signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) in vessel walls, lumen, and CSF, while blinded to the presence and type of BB technique used. Repeated measures ANOVA or Friedman tests were performed for the comparisons, followed by Bonferroni correction. The 3T T1WI sequences without BB are significantly superior in vessel wall delineation (P = 0.001). Black CSF scores were lower in SPACE with DANTE than SPACE without DANTE, and in BrainVIEW without iMSDE than SPACE without DANTE (P < 0.001). However, there were no significant differences in BB effect, image quality, and acceptability between the four 3D T1WI sequences (p > .05). The SNRVessel wall, CNRWall-Lumen, and CNRWall-CSF were higher (all p < .001) on SPACE with and without DANTE than on BrainVIEW with and without iMSDE. SNRLumen were higher (all p < .001) on BrainVIEW with and without iMSDE than on SPACE with and without DANTE. SNRCSF was higher (all p < .001) on BrainVIEW with iMSDE than on SPACE with DANTE. Both 3D TSE T1WI sequences were acceptable for intracranial vessel wall evaluation, with or without BB techniques. Therefore, BB techniques may not necessarily be required with 3D TSE T1WI with a long ETL and TR (below 1160 ms).